2021
DOI: 10.1002/cam4.3970
|View full text |Cite
|
Sign up to set email alerts
|

The global burden of thyroid cancer and its attributable risk factor in 195 countries and territories: A systematic analysis for the Global Burden of Disease Study

Abstract: Background Thyroid cancer is a growing threat to human health. Few studies have explored trends of thyroid cancer and relationships with social development factors. In this study, we explored the trend and relationship based on GBD. Methods By using GBD study, we obtained detailed data of thyroid cancer. Incidence, mortality and DALY were used to assess epidemiological characteristics. ASR and EAPC were used to estimate the trend. Results Globally, the incidence significantly increased from 1990 to 2017, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 33 publications
2
45
1
Order By: Relevance
“…For attributable risk factors, the impact of high body‐mass index on DALYs from thyroid cancer was greater in males than in females in different regions. Compared with previous GBD studies, 4 , 5 , 6 , 7 we used up‐to‐date epidemiological data to investigate the burden of thyroid cancer, examined the association between the SDI and incidence, mortality, and DALYs of thyroid cancer, and clarified the disparity of attributable risk factors for DALYs due to thyroid cancer in the GBD region. In addition, this study covered more locations and data sources, including 204 countries and territories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For attributable risk factors, the impact of high body‐mass index on DALYs from thyroid cancer was greater in males than in females in different regions. Compared with previous GBD studies, 4 , 5 , 6 , 7 we used up‐to‐date epidemiological data to investigate the burden of thyroid cancer, examined the association between the SDI and incidence, mortality, and DALYs of thyroid cancer, and clarified the disparity of attributable risk factors for DALYs due to thyroid cancer in the GBD region. In addition, this study covered more locations and data sources, including 204 countries and territories.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the burden of thyroid cancer based on the Global Burden of Disease (GBD) 2017 data. 4 , 5 , 6 , 7 The GBD 2019, with its up to date population‐based cancer registry data and methodological refinements, provides the most comprehensive estimates of thyroid cancer burden. 3 , 8 , 9 , 10 Compared with previous studies, the added value of this study is that cancer registry data have been added from more countries and the minimum age group has been updated (5–9 years old).…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing prevalence of DTC and the application of thyroid ultrasound around the world, thousands of patients were admitted to the hospital and further elect to undergo surgical intervention (5,6). However, the trend of overdiagnosis and treatment modality has aroused wide concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, the standardized clinical management for papillary thyroid carcinoma (PTC) has aroused wide concern in global researchers (1)(2)(3), due to the significant increasing prevalence and overdiagnosis of thyroid cancer (4)(5)(6). According to the latest management guidelines derived from the American Thyroid Association (ATA), lobectomy without central lymph node dissection (CLND) was evaluated to be a sufficient surgical extension for clinically lymph node negative (cN0) patients with differentiated thyroid carcinoma (DTC) (3).…”
Section: Introductionmentioning
confidence: 99%
“…Research based on the Global Burden of Diseases (GBD) study of 2017 have reported an increase in the incidence of TC worldwide (8,9). However, this incidence varies greatly from country to country, and there is a so-called ''thyroid cancer epidemic'' across the developed world, in countries such as the USA (10), Canada (11), Australia (12), and Asia (3).…”
Section: Introductionmentioning
confidence: 99%